Modelling lined rock caverns subject to hydrogen embrittlement and cyclic pressurisation in fractured rock masses - Zhao, Chenxi; Yu, Haiyang; Zhang, Zixin; Lei, Qinghua (International journal of hydrogen energy, 2025)
The technology of lined rock cavern (LRC) with great geographical flexibility is a promising, cost-effective solution to underground hydrogen storage. However, the air-tight steel tanks used in this technology are susceptible to material degradation due to hydrogen embrittlement (HE), potentially leading to leakage and structural failure, especial for LRCs constructed in complex geological conditions. In this paper, we develop a 2D multiscale numerical model based on the finite element method to assess the impact of HE on the LRC performance in fractured rock masses under cyclic gas pressurisation. Within this framework, a large-scale model is used to simulate the deformation and damage evolution of both fractured rock and an LRC under in-situ stresses and internal gas pressurisation, while a small-scale model captures HE in the steel lining of the LRC. Our simulations reveal that damage in the rock, concrete, and steel degradation is strongly affected by pre-existing fractures and in-situ stresses. Our results also reveal the presence of a strong positive feedback between hydrogen concentration and stress redistribution in the steel lining. Moreover, a comparison between models with and without considering HE illuminates that hydrogen concentration significantly contributes to steel degradation, particularly during the long-term LRC operation, highlighting the critical role of HE in the safety and performance of the LRC. The findings and insights obtained from our work have important implications for the design optimisation and performance assessment of LRCs for sustainable underground hydrogen storage. •A multiscale model is developed to simulate lined rock caverns for hydrogen storage.•Interaction between the cavern and its surrounding fractured rock mass is captured.•Effects of hydrogen diffusion and embrittlement in steel linings are considered.•Fractures in rock exert a strong control on damage in concrete and steel linings.•Interplay of hydrogen accumulation and stress concentration drives steel degradation.